Збільшення рівномірності розподілу добрив відцентровим робочим органом - Дурман, С. М. (My University, 2017)
UK: Обґрунтовано необхідність регулювання внутрішнього краю лопатки відцентрового робочого органу машин для внесення мінеральних добрив. EN: For the increase of equitability of mineral fertilizers during work of ma-chine with centrifugal vehicles on that the shoulder-blades of different length are set, it is necessary to regulate the internal edge of shoulder-blades with the purpose of capture of certain dose of fertilizers.
Increase of equitability by centrifugal working organ of fertilizers
Keywords: врожайність; добрива; розподіл; нерівномірність; зона подач; радіус лопатки